2020
DOI: 10.1177/0004563220935140
|View full text |Cite
|
Sign up to set email alerts
|

Functional vitamin B12 deficiency in phenylketonuria patients and healthy controls: An evaluation with combined indicator of vitamin B12 status as a biochemical index

Abstract: Background Vitamin B12 deficiency frequently appears in phenylketonuria patients having a diet poor in natural protein. The aims of this study were to evaluate vitamin B12 status in phenylketonuria patients by using combined indicator of vitamin B12 status (cB12) as well as methylmalonic acid and homocysteine, more specific and sensitive markers, in comparison with healthy controls. Methods Fifty-three children and adolescents with phenylketonuria under dietary treatment and 30 healthy controls were assessed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 47 publications
(103 reference statements)
0
11
0
Order By: Relevance
“…There was no consistent relationship between metabolic control and MMA and Hcy levels, although there were significant correlations between serum vitamin B12 and Hcy, MMA, and metabolic control. Using a combined calculation of vitamin B12, Akış et al (2020 ) found lower vitamin B12 in 24.5% of PKU patients and 13.3% of controls, but this difference was not significant.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…There was no consistent relationship between metabolic control and MMA and Hcy levels, although there were significant correlations between serum vitamin B12 and Hcy, MMA, and metabolic control. Using a combined calculation of vitamin B12, Akış et al (2020 ) found lower vitamin B12 in 24.5% of PKU patients and 13.3% of controls, but this difference was not significant.…”
Section: Discussionmentioning
confidence: 95%
“…MMA levels did not differ significantly, with values within the normal range. Akış et al (2020 ) found higher MMA concentrations in a PKU group than controls. MMA concentrations were high in 56.5% of the patients and 26.7% of the controls with normal vitamin B12 levels.…”
Section: Discussionmentioning
confidence: 96%
“…The included studies were published from 1994 [38] to 2023 [39], and their characteristics are detailed in Table 1. Four studies were conducted in Greece [25,27,40,41], three in Turkey [31,42,43], three in Spain [32,44,45], two in Austria [26,46], two in Chile [39,47], two in Japan [29,30], two in the United Kingdom [48,49], two in the USA [38,50], and one each in Germany [51], France [52], Poland [28], and Switzerland [53]. All studies, except for one case-control study [26], were cross-sectional and compared individuals with PKU to healthy controls.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Five studies assessed children [25,27,28,31,40], one studied adolescents [43], children and adolescents were included in nine studies [26,32,38,41,42,45,46,50,51,53], six studies examined adults [29,30,39,48,49,52], and the remaining two studies had a mixed population [44,47]. Most studies included males and females [24,[26][27][28][29][30]37,38,[40][41][42]45,46,[49][50][51][52], and while it was not explicitly stated in other studies [25,27,40,44,45,48,49], they likely involved both male and female participants. Table 2<...…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Plasma MMA analysis: Plasma samples were collected in tubes containing EDTA anticoagulant and were centrifuged immediately at 4°C and 2000xg for ten minutes. The concentration of MMA was measured by LC-MS/MS (Shimadzu Prominence UFLC, Japan and 4000 QTRAP, Applied Biosystems, Germany, respectively), as described previously [11]. Intra-and inter-day MMA precisions were <3.8% and <5.7%, respectively.…”
Section: Lc-ms/ms Analysismentioning
confidence: 99%